2017
DOI: 10.2134/agronj2016.06.0345
|View full text |Cite
|
Sign up to set email alerts
|

Response of Six Turfgrass Species and Four Weeds to Three HPPD‐Inhibiting Herbicides

Abstract: Core Ideas Tembotrione controlled weeds selectively in bluegrass, fescue, and zoysiagrass turf. Topramezone controlled key weeds better than mesotrione and tembotrione. Topramezone was among the safest herbicides on four of the six turfgrasses tested. Results will aid herbicidal‐risk assessment near potentially sensitive turfgrass species. The study supports considerations for herbicide label expansion or registration in turf. Mesotrione (2‐[4‐(methylsulfonyl)‐2‐nitrobenzoyl]‐1,3‐cyclohexanedione), tembotrione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…y Regimen of mesotrione (140 g·ha -1 ) + amicarbazone (100 g·ha -1 ) followed by mesotrione only (140 g·ha -1 ) 2 weeks later. Brewer et al (2017) demonstrated that mesotrione causes more CBG injury than topramezone, CBG injury from topramezone + triclopyr tank mixtures was similar to mesotrione + triclopyr tank mixtures on all observation dates in 2014 and 2015.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…y Regimen of mesotrione (140 g·ha -1 ) + amicarbazone (100 g·ha -1 ) followed by mesotrione only (140 g·ha -1 ) 2 weeks later. Brewer et al (2017) demonstrated that mesotrione causes more CBG injury than topramezone, CBG injury from topramezone + triclopyr tank mixtures was similar to mesotrione + triclopyr tank mixtures on all observation dates in 2014 and 2015.…”
Section: Resultsmentioning
confidence: 85%
“…Nonsignificant when a # 0.05. and 9 WAIT in 2016. The injury was likely caused by the triclopyr, as previous research by Brewer et al (2017) demonstrated that topramezone and mesotrione cause little to no kentucky bluegrass injury. Although we cannot make a direct statistical comparison between fall and spring experiments in our research, amicarbazone + mesotrione caused more kentucky bluegrass injury than in the spring than in the fall experiment.…”
Section: Nsmentioning
confidence: 79%
“…In cases where transformation was needed, data were back-transformed for presentation clarity. A similar approach for determining data normality and homogeneity of variance to meet assumptions of ANOVA has also recently been used by other researchers (Brewer et al 2016; Rana and Askew 2016). All measured responses were subjected to a combined ANOVA using PROC GLM in SAS with the sum of squares partitioned to reflect the effects of the block, and also trial/location, herbicide program, and their interactions.…”
Section: Methodsmentioning
confidence: 99%
“…Topramezone can control goosegrass, crabgrass, and dallisgrass at any growth stage (Anonymous 2018a). Topramezone is a hydroxyphenylpyruvate dioxygenase (HPPD) inhibitor associated with whitening or bleaching symptoms on the newest tissue in sensitive plant species (Brewer et al 2017;Goddard et al 2010;Grossmann and Ehrhardt 2007). Topramezone was initially registered in 2013 for bermudagrass and goosegrass removal from cool-season turfgrasses (Anonymous 2018a).…”
Section: Introductionmentioning
confidence: 99%